Mucoadhesive buccal tablet of leuprolide and its fatty acid conjugate: Design, in vitro evaluation and formulation strategies - Jin, Hyomin; Ngo, Hai V.; Park, Chulhun; Lee, Beom Jin (International Journal of Pharmaceutics, 2023)
This study aimed to design mucoadhesive buccal tablets of leuprolide (LEU) and to manufacture and evaluate the properties of buccal tablets containing LEU-oleic acid conjugate (LOC) and self-assembled LEU-oleic acid nanoparticles (LON), which were developed in a previous study. Hydroxypropyl methylcellulose (HPMC 4000) was used as the mucoadhesive polymer, and tablets were prepared by direct compression. The formulations were characterized by weight, content uniformity, thickness, hardness, swelling index, disintegration time, mucoadhesion time, and drug release. The chosen formulation maintained an adhesion time of up to 6.43 h and a disintegration time of 4.10 h. Drug stability in the mucoadhesive tablets was confirmed after 2 h of storage in human mimic saliva (Phosphate buffer solution pH 6.8). Furthermore, the designed LEU formulation and the LOC and LON developed in a previous study were prepared as buccal tablets and compared. In the dissolution and permeation studies, LON-loaded buccal tablets showed the highest permeation rate. This study suggests that mucoadhesive buccal tablets containing self-assembled LON may effectively increase the medication adherence for pediatric and geriatric patients by improving the bioavailability and permeation rate of LEU.
Keywords: Adhesiveness; Administration, Buccal; Aged; Child; Fatty Acids; Humans; Leuprolide; Mouth Mucosa; Oleic Acid; Tablets; Dissolution; Fattigation-platform; Formulation design; Leuprolide-oleic acid conjugate; Mucoadhesive buccal tablets; Permeation enhancer; Self-assembled nanoparticle